Analysis of Body Posture, Environment and Workload on Neck and Shoulder Pain Complaints in Nurses at Cendrawasih Dobo Regional Hospital - Kristo Marco Rumangun; Indasah Indasah; Novita Anna Anggraeni (Eduvest - Journal of Universal Studies, 2024)
Nurses in hospitals often face work challenges such as non-ergonomic posture, less than ideal work environment, and heavy workload, which can trigger neck and shoulder pain complaints. This problem not only affects the health and productivity of nurses, but can also affect the quality of health services provided to patients. This study was conducted to analyze the relationship between posture, environment, and workload on neck and shoulder pain complaints in nurses at Cendrawasih Dobo Hospital, in order to provide recommendations for improving more ergonomic working conditions. This study used an observational design with a cross-sectional approach to analyze the relationship between posture, environment, and workload on neck and shoulder pain complaints in nurses at Cendrawasih Dobo Hospital. The REBA method was used to evaluate ergonomic risks, with data collection through questionnaires analyzed using univariate, bivariate, and multivariate analysis. The study was conducted in September-October 2024 with a total sampling technique on the entire population of 140 nurses in the hospital. The results showed that there was a significant relationship between body posture (p-value 0.000, correlation 0.538) and workload (p-value 0.000, correlation 0.442) with neck and shoulder pain complaints, where the worse the body posture and the heavier the workload, the higher the pain complaints. In addition, a non-standard work environment, such as low lighting (52-348 lux) and high noise (> 45 dB), also increased the risk of these complaints. These findings emphasize the importance of improving ergonomics and work environment conditions to improve the health and well-being of nurses.